Short-term changes in dietary sodium intake influence sweat sodium concentration and muscle sodium content in healthy individuals. Issue 1 (January 2020) - Braconnier, Philippe; Milani, Bastien; Loncle, Nicolas; Lourenco, Joao M.; Brito, Wendy; Delacoste, Jean; Maillard, Marc; Stuber, Matthias; Burnier, Michel; Pruijm, Menno
Abstract : Objective: There is increasing evidence that sodium can be stored in the skin and muscles without being osmotically active, yet whether acute changes in dietary sodium intake alter sweat and muscle sodium content has not been investigated previously. Methods: In a cross-over design, we assessed muscle sodium content by 23 Na-MRI in 38 healthy normotensive volunteers (aged 33.5 ± 11.1 years, 76.3% women) after 5 days of high-sodium diet (6 g of salt added to their normal diet) and 5 days of a low-sodium diet. In a subgroup of 18 participants (72.2% women) we conducted quantitative pilocarpine iontophoretic sweat collections and measured the sodium concentration in sweat. Plasma aldosterone and plasma renin activity levels were measured in all participants. Results: Under high-sodium diet conditions urinary sodium excretion, muscle sodium content and sweat sodium concentration all increased significantly. Muscle sodium content ( r m = 0.47, P = 0.03) and sodium sweat concentration ( r m = 0.72, P < 0.001) correlated positively with salt intake as estimated by 24-h urine sodium excretion. Age, sex or the phase of the menstrual cycle did not influence muscle or sweat sodium concentrations or their changes. In contrast, plasma aldosterone levels were negatively associated with both muscle sodium ( r s = −0.42, P = 0.0001) and sweat sodium content ( r s = −0.52, P = 0.002). Plasma renin activity correlated negatively with sweat sodium ( r s = −0.43, P = 0.012) and muscle sodium levels ( r s = −0.42, P < 0.001). Conclusion: Muscle and sweat sodium concentrations are significantly higher on a high-salt intake in healthy male and female individuals, suggesting that muscle and sweat play a role in regulating sodium balance in humans. Abstract : Supplemental Digital Content is available in the text